Peran Pemerintah Desa dalam Pemberdayaan Petani di Desa Sungai Dua Indah Kecamatan Rambah Hilir Kabupaten Rokan Hulu - Alfajri, Gayos (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
This study aims to determine the role of village government in empowering farmers in Sungai Dua Indah Village, Rambah Hilir District, Rokan Hulu Regency. Especially the role of the Village Government in empowering farmers as a Regulator, Dynamicator, and Facilitator in empowering farmers in Sungai Dua Indah Village. The method used in this study is a qualitative descriptive method with informants consisting of Field Agricultural Extension Officers, Village Heads, BPD Chairmen, Farmer Group Leaders and Community Leaders with a total of 8 informants and data collection tools used in the form of observation, interviews, and documentation. The results showed that the role of the village government in empowering farmers in Sungai Dua Indah Village has been running but has not been fully optimal and has not been in accordance with the expectations of farmers. When viewed from the aspect of Village Government as a Regulator, Sungai Dua Indah Village Government has implemented existing rules in accordance with regulations set by the Central and Regional Governments. on the Dynamicator aspect with subindicators of Socialization, Mentoring, Training, and Field Visits. The results showed that the Sungai Dua Indah Village Government has not been fully implemented. Furthermore, in the Facilitator aspect, namely the provision of assistance, the role of the village government as a dynamicator and facilitator has been running, but it has not been optimal because there are still many farmers in Sungai Dua Indah Village who have not received training, socialization, seed subsidies, fertilizer subsidies and agricultural equipment assistance that has never been given to farmers in Sungai Dua Indah Village.